GRAMMATICAL ERROR ANALYSIS IN ENGLISH WRITING A CASE STUDY AT REKTOR PRIVATE INSTITUTE ENGLISH COURSE - Sri Khaerani Rahman (Publikasi dan UKI Press UKI Toraja., 2022)
This research aimed to investigate and reveal the grammatical error in English Writing made by the students in one of English Course in Makassar and how those errors appeared in a sentence. The writer also focused on the most frequent type of grammatical error and some other possible errors in English Writing. The writer used descriptive quantitative method to analyze the data which were found in the sentences. The writer used random sampling technique to choose which samples were to be analyzed. The data were determined according to the needs and purposes of this research. The writer found thirty-five samples. In this case, the writer used two methods of collecting data, library research and field research. After doing the analysis, the research result indicates that the most frequent error made by the students in English Writing in case of four types which occurs in this study. Omission, addition, malformation, and disordering are in the use of simple present tense. This thesis reveals that nearly 50% students of all subjects make many errors in it.